PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. MASSCOM GRAPHY SEMARANG - Aji, Oki Prasetyo; Suryoko, Sri; Budiatmo, Agung (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated by the human resources play an important role in realizing the performance of a company. Companies are required to improve the performance of employees in order to output the resulting competitive. PT. Masscom Graphy Semarang is a company engaged in the printing and publishing of daily newspapers and magazines so need to maintain human resources work in order to meet the quality and quantity product. However, in 2013 an increase Missdruk in the work of the PT. Masscom Graphy Semarang which causes a decline in the quality and quantity of production.The purpose of this study was to determine the effect of the work environment, work discipline, and compensation for the performance of PT. Masscom Graphy Semarang. This type of research is explanatory, with technique of collecting data through using interviews, questionnaires and library research. The sampling technique using disproportionate random sampling technique. Sample of 60 people who are employees of the production of a wide - range of sub-section. This study used a qualitative analysis techniques and quantitative analysis. Quantitative analysis using validity, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, cross tabulation, as well as the significance test (t test and F test).Results of this study variable working environment variable is good, variable labor discipline is exceptionally high, and variabel compensation is relatively adequate and the variable performance is excellent .The results of this study all independent variables, namely the work environment (X1), labour discipline (X2), and compensation (X3) together (simultaneously) or individually (partial) affect employee performance dependent variable (Y).Suggestions in this research that the company should pay attention to hygiene in the workplace, improve regulatory oversight of the work, and reviewing the compensation following the employee's needs, and maintaining the quality and quantity of printing as a result of employee performance and the need for further research by the company or outside the company about the variables - other independent variables that can be considered to provide an additional contribution to improving employee performance.